Climate change adaptation, gender, and mainstreaming: The role of gender in Fiji's relocation initiative - Bertana, Amanda; Blanton, Natalie (Climate and Development, 2022)
Climate change has elucidated already existing gender inequalities associated with unequal access to resources, decision-making processes, and higher exposure to environmental shocks and stressors. Growing acknowledgment of the gender-differentiated implications of climate change in recent years has placed gender equality as a focal point in international discourses on climate change adaptation. The policy perspective of gender equality is universalized, but how it transcribes in local climate change adaptation projects remains elusive. Using the relocation of Vunidogoloa, Fiji, this article explores the tension and compatibility between the way gender equality is discussed and how it is implemented in climate change adaptation projects. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; changements climatiques; discipline; environnement; ethnographie; fidji; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; sécurité alimentaire; thématiques

Women's invisible work in disaster contexts: Gender norms in speech on women's work after a forest fire in Sweden - Danielsson, Erna; Eriksson, Kerstin (Disasters, 2022)
The aim of this study is to investigate what women do in disaster situations and how both men and women perceive and discuss the work of women. These patterns were evidenced in the stories that were told following the largest forest fire in the modern history of Sweden in July 2014. The study is based on 31 retrospective interviews with volunteers involved in combating the forest fire and concentrates on stories about the supportive work of women during this disaster. The results indicate that women were praised when they followed traditional norms but were denigrated when they performed what were viewed as male-coded tasks. The stories reveal norms concerning what a woman is and is not by focusing on women's age and clothing and by directly and indirectly questioning their abilities and authority. The norms are also rendered visible by the positive attention that women receive while describing doing what is expected of them
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; catastrophe naturelle; division sexuelle du travail; environnement; europe; normes de genre; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; stéréotypes de genre; suède; thématiques; travail

Climate–urban nexus: A study of vulnerable women in urban areas of KwaZulu-Natal province, South Africa - Hlahla, Sithabile; Simatele, Mulala Danny; Hill, Trevor; Mabhaudhi, Tafadzwanashe (Weather, Climate, and Society, 2022)
The changes in climatic conditions and their associated impacts are contributing to a worsening of existing gender inequalities and a heightening of women’s socioeconomic vulnerabilities in South Africa. Using data collected by research methods inspired by the tradition of participatory appraisals, we systematically discuss the impacts of climate change on marginalized women and the ways in which they are actively responding to climate challenges and building their adaptive capacity and resilience in the urban areas of KwaZulu-Natal, South Africa. We argue that changes in climate have both direct and indirect negative impacts on women’s livelihoods and well-being. Less than one-half (37%) of the women reported implementing locally developed coping mechanisms to minimize the impacts of climate-related events, whereas 63% reported lacking any form of formal safety nets to deploy and reduce the impacts of climate-induced shocks and stresses. The lack of proactive and gender-sensitive local climate change policies and strategies creates socioeconomic and political barriers that limit the meaningful participation of women in issues that affect them and marginalize them in the climate change discourses and decision-making processes, thereby hampering their efforts to adapt and reduce existing vulnerabilities. Thus, we advocate for the creation of an enabling environment to develop and adopt progendered, cost-effective, transformative, and sustainable climate change policies and adaptation strategies that are responsive to the needs of vulnerable groups (women) of people in society. This will serve to build their adaptive capacity and resilience to climate variability and climate change–related risks and hazards. © 2022 American Meteorological Society.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afrique du sud; approches et analyses; changements climatiques; environnement; histoire et politique; patriarcat; pauvreté; projet charge mentale; périodes historiques; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Représentation des femmes expertes en environnement dans les médias écrits québécois – Boutique - Réseau femmes et environnement (2022)
Les femmes expertes en environnement sont-elles sous-représentées dans les médias écrits québécois❓ C’est pour répondre à cette question que le Réseau des femmes en environnement a réalisé une étude exploratoire sur le sujet. Dans le cadre de cette étude : ➾ La littérature et les données récentes sur le sujet ont brièvement été explorées; ➾ 125 articles québécois tirés de la revue de presse produite par Copticom pour sa communauté de pratique en communication climatique ont été analysés ; ➾ Dix entrevues individuelles ont été menées auprès de journalistes et de femmes expertes souvent citées dans les médias relativement à des enjeux environnementaux ou de santé. Le Réseau a été accompagné dans cette démarche par Selma Vorobief, conseillère en évaluation participative et en recherche-action.
Keywords: 2000 à aujourd'hui; amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; discipline; environnement; médias; périodes historiques; québec; régions géographiques; santé; sciences; systèmes d'oppressions; thématiques; travail; violences